Use of HPV testing in cervical cancer screening services in Mexico, 2008-2018: a nationwide database study - Erika Hurtado-Salgado; Eduardo Ortiz-Panozo; Jorge Salmerón; Nenetzen Saavedra-Lara; Pablo Kuri-Morales; Eduardo Pesqueira-Villegas; Rufino Luna-Gordillo; Eduardo L Franco; Eduardo Lazcano-Ponce (Instituto Nacional de Salud Pública, 2018)
Objective. To describe the methods of a study aimed at evaluating high risk-HPV (hrHPV)-based screening and cervical cytology as triage compared to conventional cervical cytology as primary screening in the detection of grade 2+ cervical intraepithelial neoplasia in the National Cancer Screening Program (NCSP) of Mexico. Materials and methods. We will use information originated from the Womens Cancer Information System of Mexico regarding cervical cancer from 2008 to 2018. The database includes cytology results, diagnostic confirmation by histopathology and/or treatment colposcopy. We will then carry out statistical analyses on approximately 15 million hrHPV. Results. We will evaluate the overall performance of hrHPV-based screening as part of the NCSP and compare hrHPV-based to cytology-based screening under real-life conditions. To guarantee an unbiased comparison between hrHPV with cytology triage and conventional cytology we will use propensity score matching. Conclusion. Decision makers may use our results to identify areas of opportunity for improvement in NCSP processes.